Women advertising practitioners in Malaysia: views on career satisfaction - Mohd Helmi Abd Rahim,; Foong, Zaai Yee; Normah Mustaffa, (Universiti Kebangsaan Malaysian, 2010)
Much has been said about gender differences in the professional field. In fact, patriarchal societies like Malaysia, is said to have a great deal of biasness favoring males still exist. It is pleasing to note that there is a profession, where gender discrimination hardly exists, and that is advertising. Moreover, advertising is an industry dominated by women in Malaysia. Somehow, women have no problem climbing up to the top. However, advertising is a fast-paced industry which highly demands countless efforts, enthusiasm and sheer perseverance in order to succeed. The research investigates the level of career satisfaction among women advertising practitioners in Malaysia, and determines the specific factors that make them stay or leave the industry. In-depth interviews via the focus group method were done with thirty respondents as to gather data which are more personalized, more in-depth, spontaneous and comprehensive.The respondents were categorized into three groups,namely, veteran, junior and advertising major women students who have had once or twice internship experiences in any advertising agencies. Results indicated that on the average, there is a relatively an average level of job satisfaction among the respondent. Veteran women advertising practitioners showed a higher level of satisfaction whereas the junior respondents generally have low level of satisfaction. Consequently, the undergraduate advertising students had also shown a relatively low level of satisfaction towards their internship experiences. Suggestions from the respondents will be able to provide guidelines for advertising agencies to handle and maintain their women staffs’ work enthusiasm and satisfaction for a better organizational commitment